Organización contable en la empresa del señor Goberth Armando Davila Feijoo de la ciudad de Piñas. Periodo del 01 de abril al 30 de junio del 2022. - Luzuriaga Jiménez, Mayti Karina (2023)
The present entitled work: Contable organization in the company of mrs Goberth Armando Davila Feijo in Piñas city. Period from 01st to 30th june of 2022., it was developed with the main purpose of get the Engineer in Accountant and Audit Public Accountant Auditor title, according to the National University Academic Regime gift and to know the economic and financial information on curse or evolution from the daily activities that the company to through the obtained results as a result of the countable process in agreement about what the rule establish. To accomplish the objectives, it was developed and analysis of the spin and nature of the business, also some type of politics o directions given, that makes happened the developing of an account plan base in the needs with the respective coding that makes easier to identify the counts at the moment of register the accounting records; base on this account detail it was made the manual where it describes each of the specific movements of debit and credit and also the balance. Next, it was developing the initial inventory through the physical and counting checking of each of the assets, rights and obligations that the company has in an order and detail way allowing to know the value of the merchandise for the develop of its daily activities, given a total of credit of $ 241.356,37, in debit $ 102.552,98 and with a heritage of $ 138.8.3,39, that allow to elaborate the initial balance sheet as start point to elaborate the countable process. Finally, the countable process it could develop, and for that it was done the respective collection, classification and registration of the previous auxiliaries elaborated in base on the paper work given by the factory, starting with the initial inventory and base situation of the balances with the data that form part of the credit and debit and the heritage; witch balance in total were order taking into account the time and the system from 01st April until 30th of June of 2022, considering the system of multiple heritage, with this information it was develop the main book in which one it was control in separate way the movements of debit and credit in each countable count that appears in daily in general; the balance of the checking balance that was use to obtain the detail analysis from the total list of the credit and debit of accounts checking the balance are 3 accurate, reasonable and reliable; adjust that allow present reasonable balance of the counts through the timely and proper purification; work sheet that give place of the elaboration, financial stares given a reasonable vision of the economic and financial company , the cash flux and the heritage evolution, the financial state that reflects a total of credit of $ 227.855,58; debit of $ 96.355,10 and a heritage of $ 131.500,48, the same decreased due to exercise deficit, as the state of results shows a total of income of $ 18.243,17; 5 expenses of $ 25.546,07 to get a total lost of the period of $ 7.302,91 and related with the cash flux a total of amount of the period of $ 36.454,95 and extra data is that the owner make appropriate decisions base on the progress of the company